2016
DOI: 10.1111/1440-1630.12284
|View full text |Cite
|
Sign up to set email alerts
|

The Community Integration Questionnaire – Revised: Australian normative data and measurement of electronic social networking

Abstract: The addition of electronic social networking items to the CIQ-R offers a contemporary method of assessing community integration following ABI. Normative CIQ-R data enhance the understanding of community integration in the general population, allowing occupational therapists and other clinicians to make more meaningful comparisons between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…The research has added further to the emerging evidence comparing community integration outcomes of adults with neurotrauma with Australian general population CIQ‐based norms (Migliorini et al ., , early online). Previous research has identified individual priorities for each domain of community integration may vary by age and gender, and be influenced by living location and situation (Callaway et al ., ; Sander, Clark & Pappadis, ). The effects of such demographic variables on integration outcomes have traditionally been hard to unravel.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The research has added further to the emerging evidence comparing community integration outcomes of adults with neurotrauma with Australian general population CIQ‐based norms (Migliorini et al ., , early online). Previous research has identified individual priorities for each domain of community integration may vary by age and gender, and be influenced by living location and situation (Callaway et al ., ; Sander, Clark & Pappadis, ). The effects of such demographic variables on integration outcomes have traditionally been hard to unravel.…”
Section: Discussionmentioning
confidence: 99%
“…As part of revision of the CIQ, large scale normative CIQ-R data has been gathered with Australian adults of working age, and converted to CIQ normative data for use with the original scale (Callaway et al, 2015c;. The development of normative data provides opportunity for comparison of CIQ scores of people with disability to matched norms, allowing interpretation of an individual's score relative to the general population.…”
Section: Ciq Normative Data and Normative Data Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-six articles were excluded because they were follow-up articles of a previous article about the same instrument. Five instruments claimed to measure at the level of participation, but did not clearly indicate the name of the instrument and were excluded: the WHO-Disability Assessment Schedule 2.0 (WHO-DAS 2.0) (98,99), the Life habits (Life-H) (91, 100), the Life habits for children (Life-H children) (101), the Community Integration Measure (102) and the Community Integration Questionnaire-Revised (CIQ-R) (103). Twenty-six instruments had participation in their title; 6 of which were excluded because of the combined words and narrowing the concept to social or community participation in the title: Australian Community Participation Questionnaire (ACPQ) (104), the Maastricht Social Participation Profile (MSPP) (105), the Activity & (community) Participation Questionnaire (APQ) (106), the Temple University Community Participation (TUCP) (107), the Community Participation Domains Measure (CPDM) (108) and the ICF Mental activities and Participation Measure (ICF-Mental-A&P) (109).…”
Section: Different Ways To Measure Participationmentioning
confidence: 99%